From motivation to experience: How advertising and income influence urban park tourism in sub-saharan Africa: A case study of Agodi parks and gardens, Ibadan - Adeyemo, Tosin P. (Journal of Commerce, Management, and Tourism Studies, 2025)
The study evaluates the shift from Motivation to Experience: How Advertising and Income Influence Urban Park Tourism in Sub-Saharan Africa - A Case Study of Agodi Parks and Gardens, Ibadan. The data for this study were collected both from the primary and secondary sources. A pilot survey of the population was conducted to determine the sample size. The study used a sample size of Seventy-three questionnaires which were administered and sixty four were returned and analyzed. The research technique used for the collection of data for this study is the purposive sampling technique which makes it easier to collect data. The data was analyzed manually through the use of frequency and simple percentage tables, tables were used in presenting the data. Research findings show that advertisement motivates consumers to keep patronizing the destination, more income will influence the patronage behavior of the consumer and it also show that consumers are motivated to keep patronizing the site with other factors such as Proximity, Services rendered, Facilities in the site, Nature friendly environment, Accessibility, Fun and entertainment, Relaxation and Affordability. Hence, the study recommends that there is need for destinations to embark on advert campaign by using jingles that arouse the interest of their prospective customers; formal advertising policy that motivates/influences the patronage decision of consumers must consider adverts that appeal to them and this must equally be initiated, a proactive and effective advert process for established tourism sites should be designed and implemented. In formulating advertising policies, companies must emphasize other factors that motivate consumers to patronize the destination more in terms of Proximity, Services rendered, Facilities in the site, Nature friendly environment, Accessibility, Fun and entertainment, Relaxation and Affordability and lastly the study recommends that there is need for an improvement in the economy to empower the consumers to enable them make more patronage to the park.